Adolescence and youth: theoretical repositionings - Urteaga Castro-Pozo, Maritza (2019)
Between the end of the 19th century and a large part of the 20th century, scientific knowledge about young people was based on the theoretical triad «biological-medical-psychological», it is one of the most important scenarios in the construction of youth and is a field of dispute between different epistemic postures. Although youth and adolescence continue to be used indistinctly, they are divergent concepts since they come from two ways of looking at young people and propose different approaches and interpretations from their problems. The objective of the text is to mark the divergent trajectory of both concepts, to trace their genealogy and to enter the regime of truth that sustains the representations, institutional practices and the common sense of the population towards the youth of the 21st century. We discuss the problems that these notions pose to the recording and interpretation of contemporary youth behaviors in the face of the last great change in the social reference regime and two case studies of segments of Mexican youth are presented to illustrate the difficulties and the possible theoretical solutions to the current impasse between theory and reality.